Regulation of Public Finances in Romania in Light of Financial Constitutionality - Brad, Ion (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
Modern constitutions try to achieve a balance between establishing and restraining power. These two opposite tendencies also dominate the entire matter of public money. Consequently, our present study will be divided in two parts. In the first one we will highlight all the means provided by the Romanian Constitution so that the public authorities can have at their disposal the finance they need. In the second part we will focus on the counterpart provisions, those that try to establish a severe system of limitation and control on the whole financial activity of the state. Besides the constitutional texts, we will explore the vast jurisprudence of the Constitutional Court, which in time has provided useful explanations and clarifications upon these texts. Having this constitutional exposition as our focus and essential framework, we will extend our study to the relevant financial legislation. The constitutional norms are in this matter, as in many others, only the basic structure upon which the subsequent legislation is developed. The result will be, hopefully, a substantial presentation of the Romanian financial law centred on its constitutional regulation.KEYWORDS: Public finance, Taxation system, Fair distribution of the tax burden, Budget law, Court of Audit.